ANALISIS MUTU BIJI PALA (Myristica fragrans H.) PADA BERBAGAI TINGKAT KEMATANGAN BERBEDA SETELAH PENJEMURAN - Awuy, Gebby; Longdong, Ireine A.; Lengkey, Lady C. Ch. E. (Jurnal Teknologi Pertanian (Agricultural Technology Journal, 2020)
AbstractThe objective of this study is to investigate the quality of nutmeg with different degrees of maturity in sun drying based on the national quality standards in Indonesia, namely Calibrated Nutmeg (CN), ABCD (Average), shrivel, and BWP (Broken Wormy Punky). The result of this study showed that older maturity degree of nutmeg give the better quality. Nutmeg with maturity degree of 7 months contain 0 % CN, 7.16 %Â  ABCD, 13.09 % Shrivel, and 79.75 % BWP. Nutmeg with maturity degree of 8 months contain 7.90 % CN, 13.09 % ABCD, 13.3 % Shrivel, and 65.68 % BWP. Nutmeg with maturity degree of 9 months contain 30.12 % CN, 38.27 % ABCD, 20.99 % Shrivel, and 10.62 % BWP.Â Key words: quality analysis, different degrees of maturity, sun drying, nutmeg